The expansion strategy of multinacional chains - Seres Huszárik, Erika; Dobai Korcsmáros, Enikő (Univerzita Pardubice, 2014)
Retail operates as an intermediary in between the wholesale and final customers. After the change of regime in Slovakia the first multinational chains appeared and started to create their hypermarket-network throughout the country. It is well known that these international companies are getting bigger slice cleaved off of the retail market, as a daily shopping gradually supplanted by large weekly shopping trips, and as a result, of course, increased the size of the amount spent per purchase occasion. The key of the success of chains comes from appropriately selected sites. This paper examines the criteria for site selection of food chains in Slovakia. In our research, we consider the most important factors that influence the location choice (the road network coverage, the number of available income and population) as well as the penetration index to examine the current situation in the Slovak retail market. The penetration index examines the various size categories of municipalities in at least the percentage of the test facility as a commercial store network. The study ends with the research conclusions and proposals for future development.
Keywords: chain stores; site selection; Slovakia; retail market; penetration index; size category